Conflict Management Land Acquisition Dispute Handling Development Program for Tamansari Row Houses - Afifah Zulfika; Bayu Nurrohman (International Journal of Social Sciences Review, 2023)
The Tamansari Row House Development Program in the City of Bandung is a government program to fix the problems of existing slum settlements in the City of Bandung. The program from the Bandung City Government ultimately experienced conflict disputes between the community and the government. In conflict resolution efforts, conflict management as an effort to resolve land dispute conflicts that occurred in Tamansari Bandung City. This study uses conflict management theory from Wirawan which consists of 4 aspects, namely: Discipline, Consideration of Experiences and Life Stages, Good Communication, and Active Listening. The purpose of this research is to find out how efforts to resolve land disputes in Tamansari are related to the construction of row houses organized by the Bandung City Government. The research method used in this study is a qualitative method with descriptive analysis. The selection of research informants used a purposive technique. The results of this study indicate that conflict management is not optimal. The conflict regarding land status between the two parties became one of the factors that sparked the conflict, and the resolution was not optimal. The aspect of discipline shows that the two parties do not yet have a rule in common. The aspect of consideration of experiences and stages of life from the side of orderly administrative records that is not good is one of the triggers for conflicts that cannot be resolved. The aspect of good communication shows that the mediation that has been carried out has not resulted in a mutually beneficial solution. The aspect of active listening can be seen from the meeting of the two parties, both from mediation efforts, not being given space for other parties, namely the community, to convey the wishes of the community, namely the status of the land being defended.